Optimization of Ultrasound-Assisted Extraction of Total Flavonoids from Dendranthema indicum var. aromaticum by Response Surface Methodology - Lijie Zhong; Yi Liu; Bin Xiong; Lin Chen; Yaohua Zhang; Chao Li (Journal of Analytical Methods in Chemistry)
Dendranthema indicum var. aromaticum is a new species with strong fragrance and is used as a herbal medicine by Chinese folks. The abundant flavonoids play important roles in its pharmacological activities. In this study, an ultrasound-assisted method was used to extract total flavonoids (TF) from D. indicum var. aromaticum by response surface methodology. A quadratic model was developed to optimize the extraction conditions, whose accuracy was verified by statistic analysis. Ethanol and acetic acid at the volume ratio of 70% : 2% were selected as the extract solvent. The optimized extraction conditions were as follows: extraction time, 40 min; solid/liquid ratio, 1 : 23 g/mL; and temperature, 60°C. This is the first report of an efficient and easy-operating method for TF extraction from D. indicum var. aromaticum. Besides, this study provides reference for future pharmacological research on D. indicum var. aromaticum and extraction of bioactive components from other herbs.